Requirement for TAF(II)250 Acetyltransferase Activity in Cell Cycle Progression - Dunphy, Elizabeth L. (American Society for Microbiology, 2000)
The TATA-binding protein (TBP)-associated factor TAF(II)250 is the largest component of the basal transcription factor IID (TFIID). A missense mutation that maps to the acetyltransferase domain of TAF(II)250 induces the temperature-sensitive (ts) mutant hamster cell lines ts13 and tsBN462 to arrest in late G(1). At the nonpermissive temperature (39.5°C), transcription from only a subset of protein encoding genes, including the G(1) cyclins, is dramatically reduced in the mutant cells. Here we demonstrate that the ability of the ts13 allele of TAF(II)250 to acetylate histones in vitro is temperature sensitive suggesting that this enzymatic activity is compromised at 39.5°C in the mutant cells. Mutagenesis of a putative acetyl coenzyme A binding site produced a TAF(II)250 protein that displayed significantly reduced histone acetyltransferase activity but retained TBP and TAF(II)150 binding. Expression of this mutant in ts13 cells was unable to complement the cell cycle arrest or transcriptional defect observed at 39.5°C. These data suggest that TAF(II)250 acetyltransferase activity is required for cell cycle progression and regulates the expression of essential proliferative control genes.